Breaking Boundaries: Dalit Resistance and Revival in Bama’s Writings (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This paper explores the transformation of Dalit identity through the literary contributions of Bama, a pioneering Dalit feminist writer in Tamil literature. Her works, including Karukku, Vanmam, Ponnuthayi, and Those Days, chronicle the social, emotional, and political journey of Dalits from subjugation to assertion. Drawing from lived experiences and oral histories, Bama’s narratives provide a platform for voices long silenced by caste and gender hierarchies. This paper examines how Bama uses storytelling as resistance, portraying education, collective unity, and the awakening of self-worth as keys to liberation. It also evaluates how her female characters challenge patriarchal norms and contribute to the broader Dalit movement, reflecting a powerful shift from caste-based slavery to human dignity.